Analisis Wacana Kritis Model Sara Mills terhadap Berita Terbitan Tempo.Co Berjudul "Tangis Goenawan Mohamad Di MK: Seharusnya DPR Dibubarkan" - Islam, Imam Syaiful; Hamdani, Agus (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This study aims to analyze the construction of discourse on the news entitled "Tangis Goenawan Mohamad di MK: Seharusnya DPR Dibubarkan" published by Tempo.co. The critical discourse analysis approach of the Sara Mills model is used to reveal the position of subjects and objects in the text and how the reader is directed to interpret the discourse. This research shows that Tempo.co build a narrative that strengthens Goenawan Mohamad's position as an empowered subject by voicing strong criticism of the DPR. Meanwhile, the House of Representatives is placed as an object of criticism whose legitimacy and performance are questioned. The results of this study provide insight into how the media shapes public opinion through narrative structure and representation choices.